2013
DOI: 10.1021/ja404681x
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Glycocalyx-Mimetic Peptoids

Abstract: The glycocalyx of the cell is composed of highly hydrated saccharidic groups conjugated to protein and lipid cores. Although components of the glycocalyx are important in cell-cell interactions and other specific biological recognition events, a fundamental role of the glycocalyx is the inhibition of nonspecific interactions at the cell surface. Inspired by glycoproteins present in the glycocalyx, we describe a new class of synthetic antifouling polymer composed of saccharide containing N-substituted poly-pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 58 publications
(115 reference statements)
2
88
0
1
Order By: Relevance
“…20,21 Surface coatings consisting of high molecular weight polysaccharides such as dextran have been shown to reduce protein or cell adhesion to surfaces, 22,23 while modifications with short oligosaccharides or monosaccharides have also been demonstrated to have a pronounced effect on minimizing unspecific protein adsorption and biomass accumulation. [24][25][26][27] Previous work from our group showed that Galactose-modified carbon surfaces obtained via spontaneous grafting of aryldiazonium salts display an increased resistance to Bovine Serum Albumin (BSA) adsorption, compared to bare carbon surfaces. 18 Such an effect was achieved, remarkably, via immobilization of only 1-3 ML of the monosaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Surface coatings consisting of high molecular weight polysaccharides such as dextran have been shown to reduce protein or cell adhesion to surfaces, 22,23 while modifications with short oligosaccharides or monosaccharides have also been demonstrated to have a pronounced effect on minimizing unspecific protein adsorption and biomass accumulation. [24][25][26][27] Previous work from our group showed that Galactose-modified carbon surfaces obtained via spontaneous grafting of aryldiazonium salts display an increased resistance to Bovine Serum Albumin (BSA) adsorption, compared to bare carbon surfaces. 18 Such an effect was achieved, remarkably, via immobilization of only 1-3 ML of the monosaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…[54] In addition, carbohydrates are attractive because of their 'lowfouling' nature, which is particularly important for applications in protein rich environments (e.g., in blood). [55] The typically low binding affinity of carbohydrates to their receptors can be improved by multivalent presentation on a particle surface, thereby resulting in high binding avidity. [56] Galactosyl moieties have been applied to direct particles to asialoglycoprotein receptors, which are dominant on the surface of hepatocellular carcinoma HepG2 cancer cells.…”
Section: Targeting Ligandsmentioning
confidence: 99%
“…Two different approaches are mainly used to apply mussel adhesive properties in the field of biomaterials. On the one hand, modular peptides containing DOPA can be synthesized and easily modified by solid phase peptides synthesis (SPPS) (Ceylan et al, 2012;Ham et al, 2013;Tang et al, 2014). On the other hand, DOPA is incorporated into polymers or recombinantly expressed proteins (mussel foot proteins from the blue mussel (Mytilus edulis) by enzymatic hydroxylation of tyrosine residues (Hwang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, quinones result in a substantial loss of affinity to surfaces like titanium (Lee et al, 2006). Mussel derived peptides are easily modified with additional functionalities by SPPS or orthogonal click reactions, providing the possibility of exactly defining the chemical composition (Ceylan et al, 2012;Ham et al, 2013). The mussel adhesive approach was used to anchor cell-attracting as well as protein-repellent effects Wei et al, 2014;Kakinoki and Yamaoka, 2015).…”
Section: Introductionmentioning
confidence: 99%